Authentication System for Any Touch Devices Using DWT (International Journal of Engineering and Computer Science, 2017)
— In today’s world, the identification techniques based on human biometric features gaining much more importance. For e.g. Iris recognition system, face recognition system, finger print recognition system, retina scanning system, etc. Some important area of other techniques is also to recognize the human hand signature. Also, there is the requirement of some techniques which works automatically based on some standard computer algorithms for recognition. For e.g. to identify the criminal identity automatically based on biometric features. The aim of research is to develop an on-line system for signature verification using Discrete Wavelet Transform (DWT). Discrete Wavelet Transform (DWT) algorithm is used for features extraction. In online signature dynamic features are usually available. Genuine or Forgery signature is substantiating based features comparison. Each feature of an input signature is extracted using various steps discrete wavelet transform algorithm are matched against a reference signature to identify the genuine signature. The final decision of verification is made based on the matched features of both the signatures.